Just Peacemakers An Introduction to Peace and Justice - Jegen, Mary Evelyn (Mahwah Paulist Press, 2006)
Describes societal problems, and gives methods and means toward resolution. Each chapter is designed for personal study and also for use by groups. This is a useful guide for those involved or interested in social justice and the Christian call to discipl
Keywords: Christianity and justice -- Catholic Church. Nonviolence -- Religious aspects -- Catholic Church. Christian sociology -- Catholic Church